Structural optimization of lattice steel transmission towers. (15th June 2016) - Couceiro, I.; París, J.; Martínez, S.; Colominas, I.; Navarrina, F.; Casteleiro, M.
Highlights: A methodology for the optimization of real steel transmission towers is proposed. Weight is minimized satisfying the requirements imposed by the structural standards. The optimization methodology includes continuous and discrete design variables. The methodology is proved effective compared with other algorithms. Significant weight reductions are achieved in real designs of transmission towers. Abstract: This paper presents a methodology for the optimization of three dimensional truss structures and its application to supports of power transmission lines. For that purpose, an efficient modified version of the Simulated Annealing algorithm is developed. The validity of the proposed approach relies on practical and constructional features of the structures considered in this study. A first order sensitivity analysis is implemented to improve the performance of the algorithm and to avoid the computation of the large number of structural analyses usually required by the Simulated Annealing algorithm. The new SA algorithm is successfully applied in two classical benchmark problems and in a real full-scale design problem.